Analysis of Environmentally Semi Trammel Net based on Code of Conduct Responsibilities Fisheries (CCRF) in Cirebon Waters: Indonesia - Devi Nurkhasanah; Elinah; Al Bayyinah, Auliya (LPPM UNU CIREBON, 2021)
All fishing actors are required to use environmentally friendly fishing gear. The aim is to maintain the condition of fishery resources and their habitat, as well as to maintain the safety of fishermen and consumers. The research was conducted in February - April and August - September 2020 in Cirebon Regency, West Java Province. The research objective was to determine the status of the shrimp nets used by fishermen in Cirebon waters. The research method used is the survey method. Data analysis using weighting method on 9 criteria for environmentally friendly fishing gear based on Code 0f Conduct Responsibilities Fisheries (CCRF). Based on the research results, the semi trammel net used by Cirebon fishermen are included in the environmentally friendly fishing gear category with a score of 30.54.